The effect of teachers’ empowerment on government secondary schools’ performance in Konso zone, Southern Ethiopia - Tukura, Addisu; Sapo, Solomon (Frontiers in Education, 2023)
This study was conducted in government secondary schools in the Konso zone, southern Ethiopia, to investigate the effect of teachers' professional empowerment on school performance.A correlational explanatory research design and a mixed research approach were used. The participants of this study were 350 including teachers, principals, supervisors and heads of educational offices. The secondary schools and their respective principals, supervisors and educational office heads were selected purposively where as teachers were selected randomly.The participants provided written informed consent to participate in this study. Both primary and secondary data gathered through interviews, questionnaires and document reviews were used. Qualitative data were arranged into themes then analyzed and interpreted whereas quantitative data were analyzed by SPSS V.20. Among teachers in the study area, the majority (90.3%) were males and all of the principals, supervisors and education head offices were males indicating gender imbalance in the educational system. Teachers primarily (3.81±1.098) participate in decision-making by consultation, followed by their involvement in setting school goals and objectives (3.78±1.20). In-service trainings were primarily (4.03±1.14) offered to change the attitudes and skills of teachers and strengthen profession (3.78±1.20). The respondents weakly agree (3.65±1.16) that school leaders provide opportunities for teachers to work actively for better school performance. A strong positive correlation (P<0.01; R2>0.8) and interdependence was observed between teachers' empowerment and school performance. While there were positive signs regarding teachers' empowerment in the study schools, these measures were not implemented in a way that met teachers' needs. Also, the school performance activities implemented fell short of teachers' expectations, requiring further administrative action. To boost school performance, school leaders should identify teachers' needs and provide them with professional learning. Future works should consider the un studied secondary, elementary and primary schools to have a clear picture of the issues of teachers' empowerment and its effect on school performance in all the secondary schools of the study area.